Effects of an active warm-up on variation in bench press and back squat (upper and lower body measures) - Pullinger, S.; Robertson, C. M.; Oakley, A. J.; Hobbs, R.; Hughes, M.; Burniston, J. G. (Chronobiology International, 2019)
The present study investigated the magnitude of diurnal variation in back squat and bench press using the MuscleLab linear encoder over three different loads and assessed the benefit of an active warm-up to establish whether diurnal variation could be negated. Ten resistance-trained males underwent (mean ± SD: age 21.0 ± 1.3 years, height 1.77 ± 0.06 m, and body mass 82.8 ± 14.9 kg) three sessions. These included control morning (M, 07:30 h) and evening (E, 17:30 h) sessions (5-min standardized warm-up at 150 W, on a cycle ergometer), and one further session consisting of an extended active warm-up morning trial (ME, 07:30 h) until rectal temperature (Trec) reached previously recorded resting evening levels (at 150 W, on a cycle ergometer). All sessions included handgrip, followed by a defined program of bench press (at 20, 40, and 60 kg) and back squat (at 30, 50, and 70 kg) exercises. A linear encoder was attached to an Olympic bar used for the exercises and average force (AF), peak velocity (PV), and time to peak velocity (tPV) were measured (MuscleLab software; MuscleLab Technology, Langesund, Norway) during the concentric phase of the movements. Values for Trec were higher in the E session compared to values in the M session ( 0.53 °C, P < 0.0005). Following the extended active warm-up in the morning (ME), Trec and Tm values were no different to the E values (P < 0.05). Values for Tm were lower in the M compared to the E condition throughout (P < 0.05). There were time-of-day effects for hand grip with higher values of 6.49% for left (P = 0.05) and 4.61% for right hand (P = 0.002) in the E compared to the M. Daily variations were apparent for both bench press and back squat performance for AF (3.28% and 2.63%), PV (13.64% and 11.50%), and tPV (-16.97% and -14.12%, where a negative number indicates a decrease in the variable from morning to evening). There was a main effect for load (P < 0.0005) such that AF and PV values were larger at higher masses on the bar than lower ones and tPV was smaller at lower masses on the bar than at higher masses for both bench press and back squat. We established that increasing Trec in the M-E values did not result in an increase of any measures related to bench press and back squat performance (P > 0.05) to increase from M to E levels. Therefore, MuscleLab linear encoder could detect meaningful differences between the morning and evening for all variables. However, the diurnal variation in bench press and back squat (measures of lower and upper body force and power output) is not explained by time-of-day oscillations in Trec.